Identifikasi bakteri Vibrio spp. penyebab vibriosis pada udang vanname (Litopenaeus vannamei) di PT. Pilar Persada Parigi - Putra, Stevano F.P; Tumbol, Reiny A.; Undap, Suzanne L.; Kreckhoff, Reni L.; Pangemanan, Pankie N.L (e-Journal BUDIDAYA PERAIRAN, 2024)
The purpose of this study is to isolate and identify Vibrio spp. bacteria from vannamei shrimp (Litopenaeus vannamei) in PT. Pilar Persada Parigi Bajo Village, South Minahasa Regency. The research was carried out by starting with shrimp sampling from shrimp cultivation locations at PT. Persada Parigi Pillar in Bajo Village, Tatapaan, South Minahasa, North Sulawesi as many as 9 fish from 3 ponds (1 pond took 3 shrimp). The pond was recommended by the pond technician of PT. The Persada Parigi pillar is related to the condition of the pond which is suspected of having Vibrio spp. bacteria that need special attention. The shrimp samples were then taken to the Laboratory alive. During transportation, the samples were put in 3 separate containers equipped with battery aerators, then the identification of Vibrio spp. bacteria was carried out at the Laboratory of Pharmaceutical Microbiology, Faculty of Mathematics and Natural Sciences, Sam Ratulangi University and at the Manado Fishery Products Quality Control and Safety Quarantine Center. Isolation of Vibrio spp. bacteria using TCBS (Thiosulfate Citrate Bile Sucrose) agar media. The characterization of Vibrio spp. bacteria was carried out by a series of tests, namely gram staining tests (gram negative, positive and bacterial form), main tests (KOH 3%, H₂O₂ and oxidase), Oxidation/Fermentation (O/F), Glucose and Motility Indole Ornithin (MIO). The results of the isolation showed that there were 9 isolates of Vibrio spp. bacteria from 9 samples of vannamei shrimp (Litopenaeus vannamei) from 3 different ponds. The results of bacterial characteristics obtained negative grams, yellow and green colony morphology, bacil/stem cell shape, KOH 3% (-), catalase (+), oxidase (+), O/F (fermentative), indole (+), and motility (+), glucose (+) from the results identified by Vibrio spp. bacteria. Keywords: Litopenaeus vannamei, Vibrio spp., Vibriosis, isolation, identification